PENERAPAN ANALYTIC NETWORK PROCESS (ANP) DALAM MENENTUKAN PRESIDEN REPUBLIK INDONESIA BAGI GENERASI MILENIAL PADA PEMILU 2019 (P3M Politeknik Negeri Cilacap, 2018)
General elections or elections are one part of the democratic system to electÂ representatives in the people's representative institutions. The Indonesian nation on April 17, 2019 will implement a mechanism for the succession of elections to determine the president for the period 20192023. This paper discusses the decision making to elect the 2019 RI presidential candidate. The author uses the Analytic Network Process (ANP) method and is assisted by super decision software to see the consistency values of each comparison table. This method is expected to be able to help all parties, especially the millennial generation in Indonesia, to find out what factors are taken into consideration in choosing RI 2019 presidential and vice presidential candidates. The object of the research is the Cilacap State Polytechnic student of the Informatics Engineering Department in 2018. that the main factor in choosing the president and vice president isÂ popularization and the Jokowi-Ma'ruf pair is a pair chosen by millennials because they are populist.